Study of effects of surgical treatment in the larynx area on the speech signal - WSZOŁEK, Wiesław; KŁACZYŃSKI, Maciej; MODRZEJEWSKI, Maciej (Archives of Acoustics, 2008)
The speech signal emitted by humans may be a source of useful diagnostic and prognostic information. The signal may become, indirectly by some selected parameters, an additional source of information concerning the condition of the patient’s vocal tract anatomy, as well as physiology and pathology (deformation) of his/her other internal organs. The paper presents the next, consecutive stage of the authors’ research, concerning the search for additional parameters, which could be used for objective detection and registration of pathological changes in the larynx and vocal tract area.